Avaliação da qualidade ambiental do golfão maranhense por meio de variáveis biológicas, químicas e físico-químicas - SILVA, Marcelo Henrique Lopes (2019)
The reduction of aquatic biodiversity is among the main changes that occur in the natural environment, as a consequence of the disruption of the physical, chemical and biological environment, resulting in loss of quality and difficulty in maintaining environmental integrity. Studies that integrate different thematic areas are necessary to formulate consistent diagnoses that faithfully portray the status of the environmental quality of aquatic ecosystems, providing the scientific basis for management actions of these systems. In this perspective, the present work aims to evaluate the environmental quality of Golfão Maranhense using nutrient dynamics, physicochemical factors and fish community as environmental indicators. Water samples were collected from the surface using a Van Dorn water sampler, where the following hydrochemical variables were analyzed: water transparency (m), temperature (° C), salinity, conductivity (mS cm-¹), total dissolved solids. (TDS, g L-1), pH, dissolved oxygen (mg L-1), turbidity (NTU), total suspended solids (TSS) and dissolved nutrients (phosphate, nitrite and silicate). The relationships between these variables and the seasonality of the region, rainy season (January to June) and dry season (July to December), as well as the influence on the composition of fish communities were also evaluated. Fish were collected from 11 estuaries located in São Marcos, São José and Arraial bays. Samplings were performed with a trawnet in three replicates for each collection point. The results showed that the spatial and temporal variability of the physicochemical variables analyzed in this study is associated with the local dynamics governed by river flow, tidal movements, currents and meteorological events. Fluvial transportation of Maranhão State rivers and other freshwater sources in the Amazon region are apparently the main contributors responsible for maintaining nutrient availability in the Maranhão continental shelf. The composition of the Ichthyofauna of St. Mark's Bay was represented by a total of 56 species, distributed in 15 orders and 29 families. Seasonal evaluation of fish assemblage revealed no significant difference. However, there was a difference between the capture sites where Shannon abundance, biomass and diversity differed. The NMDS analysis (Multidimensional Scaling Analysis) and the ANOSIM (Similarity Analysis) test between months and between sampling sites, based on species composition, revealed a seasonal differentiation associated with rainy and drought months, as well as a spatial differentiation related to depth and hydrodynamic gradient resulting from the greater distance from the mangrove areas. Estimates of the weight-length ratio parameters consisted of a total of 2,888 specimens analyzed. The values of parameter b showed a predominance of positive allometric growth type, similar to other studies conducted in the region. Toxicological analysis did not show results that indicate high degree of bioaccumulation of trace metals in the ichthyofaunada of the region, but individual samples with levels above the established limits were verified, indicating that there is some degree of contamination in the region. The application of environmental quality parameters has proved to be a useful tool for decision-making, environmental planning and environmental quality assessment, checking for changing trends in aquatic ecosystems.